Applications of catalysts in thermochemical conversion of biomass (pyrolysis, hydrothermal liquefaction and gasification): A critical review. (August 2022) - Wu, Yujian; Wang, Haoyu; Li, Haoyang; Han, Xue; Zhang, Mingyuan; Sun, Yan; Fan, Xudong; Tu, Ren; Zeng, Yimin; Xu, Chunbao Charles; Xu, Xiwei
Abstract: Biomass is one of the most promising renewable resources, and biomass energy is also recognized as the zero-carbon emission energy. Over the past decade, thermochemical conversion technologies have been well developed to convert different types of biomass feedstocks into solid biochar, liquid fuels, and gas, in which catalysts are commonly applied. This review summarizes the types of catalysts used in three common thermochemical conversion pathways (pyrolysis, hydrothermal liquefaction and gasification), while focusing on the most recent progress in the applications of catalysts in these processes. The catalytic reaction mechanisms, catalysts deactivation and regeneration, industrial utilization, as well as the challenges and knowledge gaps for applications of catalyst in these processes are analyzed and discussed. Graphical abstract: Image 1 Highlights: Recent applications of catalysts in pyrolysis, HTL and gasification are summarized. Pyrolysis, HTL and gasification conversion technologies of biomass are introduced. Catalytic mechanisms and catalysts deactivation and regeneration are discussed. Challenges and knowledge gaps for the applications of catalysts are identified.